Lecture personal identification techniques : obe compliant - Duno, Joenard Contreras (Quezon City : Wisemans Books Trading, Inc., 2021)
"It contains thorough discussion about the science of fingerprinting, starts from overview on how the field of fingerprint started and innovated through the years. The topics here are arranged chronologically and systematically for more easier and deepest understanding of a neophyte who is studying the field of fingerprinting."
Includes bibliography.
English text.